Persepsi Jamaah Surau Ath-Thayyibah Jorong Batu Labi Terhadap Dakwah Buya Zedriwarman di Jorong Batu Labi Nagari Mungo Kecamatan Luak Kabupaten Lima Puluh Kota - Rindi Febriani; Penmardianto Penmardianto (KOLONI, 2023)
Islam is a religion of preaching, a religion that always encourages its followers to always be active in carrying out missionary activities. The progress of Muslims is very dependent and closely related to the da’wah activities carried out. The preacher is called da’wah, before the preacher gives directions to others, the preacher is required to absolutely master knowledge related to the Qur’an, al-hadith, fiqh and all knowledge that belongs to the field of religion, as well as with deep Islamic insight. Capable of resolving problems that arise in society and rectifying irregularities in matters of shari’ah law so as not to preach people to misguidance. Because all the deeds and behavior of the preacher will be a benchmark by the community. Another requirement to become a preacher is to have a healthy mentality. From the background above, a da’i should have a broad base of religious knowledges before preaching and a da’i should be mentally sound. The reseacher found facts on the ground that Buya Zedriwarman did not have formal education in religion whe he first became a preacher and his history was that he had previously been admitted to a mental hospital. However, Buya Zedriwarman’s da’wah was well received by the peoples in Jorong Batu Labi, especially in Surau Ath-Thayyibah Jorong Batu Labi until now. The research methods is field research with a qualitative descriptive approach. Informants were determined through snowball sampling technique with two types of informants. Sources of data were obtained from direct observation, inteviews and documentation studies. The results showed that the perceptions of the congregation of Surau Ath-Thayyibah towards Buya Zedriwarman’s da’wah were divided into two, namely positive and negative perceptions. Meanwhile, the factors that influence the perception of the congregation of Surau Ath-Thayyibah towards Buya Zedriwarman’s preaching include factors of needs, interests, experience, expectations, age, and work. Keywords: Perception, Congregation, Surau Ath-Thayyibah, Batu Labi, Da’wah, and Buya Zedriwarman